Proclaiming the gospel in an interfaith environment: Missiological and ecumenical approach - Peter White (HTS Teologiese Studies/Theological Studies, 2023)
Proclaiming the gospel (Christian witnessing) in an interfaith environment is an increasingly critical concern for Christians in today’s globalised society. This article intends to explore a missiological and ecumenical approach to address the challenge of sharing the message of Christ in multi-religious contexts. Drawing on missiological and ecumenical perspectives, the article makes suggestions on how Christians can engage with members of other religions through respectful and authentic dialogue. Such an approach involves recognising the values and beliefs of other religions. The words Christian witnessing, mission and evangelism were used interchangeably in the article in reference to proclaiming the gospel.